Genetic Diversity of Indonesian Physic Nut (J. curcas) Based on Molecular Marker - Darmawan Saptadi; Rr. Sri Hartati; Asep Setiawan; Bambang Heliyanto; Sudarsono Sudarsono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Various reports of molecular genetic diversity evaluation of physic nut (J. curcas) have given inconsistent results. Part of the reasons were because of the used of unrealiable markers. This study was conducted to evaluate genetic diversity of Indonesian physic nut germplasm using four types of molecular markers (RAPD, ISSR, SSR and SCAR markers). Twenty four J. curcas accessions planted in Pakuwon, Sukabumi, with various phenotypes were evaluated. Twenty eight SSR marker loci yielded monomorphic allele pattern and indicated that the evaluated accessions probably were all genetically homogeneous for the respective loci. Eight RAPD and 4 ISSR primers out of the total 31 tested primers produced scoreable markers and some (i.e. UBC 873, OPG 17, OPP 03 and OPQ 11 primers) generated polymorphics markers. Genetic similarity coefficiens among evaluated accessions ranged from 0.6 to 1.0 with a population mean of 0.9 indicating low diversity and narrow genetic background among accessions in all populations. Therefore, breeding program utilizing such population would only result in low genetic gain. Based on the evaluated SCAR markers, all accessions belonged to the non-toxic Mexican type of physic nut. This information is important inputs for designing future physic nut breeding strategies in Indonesia.